An Evaluation of Folklore Events in Serbia in Terms of Tourism - Željko Bjeljac (University of Belgrade, 2016)
In Serbia there are many traditional events based on tradition, folklore, old customs and traditional crafts and trades. Folklore events are the oldest elements in the development of tourism and provide a sufficient motive for tourist visits. On the basis of their program content, these events can be divided into folklore and folk music festivals, festivals of folk customs, and children’s folklore festivals. This paper offers a categorization of folklore events according to economic and geographic criteria; particular attention has been given to events that already are, or have great potential for becoming, a major attraction of the tourist destination in question and can thus contribute to a faster and higher-quality development of tourism.